The effectiveness of group therapy based on acceptance and commitment on reducing stress and depression symptoms of mothers of children with separation anxiety disorder - Ganji , Fatemeh; Yahyazadeh Jeloudar, Soleyman; Ranjbar , Mohammad Javad (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This research was conducted with the main purpose of determining the effectiveness of group therapy based on acceptance and commitment on reducing stress and depression symptoms of mothers of children with separation anxiety disorder. Method: The statistical population of the current research includes all mothers of children suffering from separation anxiety disorder in 2021 who referred to private medical clinics in Babol city. For sampling, a non-probability sampling method based on the purpose was used and according to the type of research, 20 mothers who had anxious children were selected (10 in the experimental group and 10 in the control group). And they participated in 8 2-hour sessions for two months starting from the 24th of April and ending on the 11th of June. The tools used are: Beck’s 21-question depression questionnaire with Cronbach’s alpha coefficient of 0.78; Perceived stress scale by Cohen (1983) with Cronbach’s alpha coefficient of 0.86 was used. In order to analyze the data, after collecting the data, it was recorded in the computer under the SPSS24 program and descriptive statistics, which included the frequency distribution and percentage, were used, and in the inferential statistics section, in order to find the effectiveness of the research components from Analysis of covariance test was used. Results: The results indicate that group therapy training based on acceptance and commitment to mothers of children suffering from separation anxiety disorder reduces depression and the effect size is (0.887); Perceived stress becomes the effect size (0.723). Conclusion: Group therapy based on acceptance and commitment can reduce depression and stress of mothers of children with separation anxiety disorder